SINERGI PENTAHELIX DALAM MEMBANGUN PEREKONOMIAN DAERAH DENGAN PENDEKATAN KEARIFAN LOKAL ERA DIGITAL DI KABUPATEN TANA TORAJA SULAWESI SELATAN - Ismawati, Linna; Madya Marampa, Adriana; Andrian Pratama, Muhammad; Maharani, Elsa (JURNAL PENGABDIAN KEPADA MASYARAKAT (ADI DHARMA), 2023)
The success of regional development cannot be separated from the synergy of various parties to collaborate in improving community welfare. The synergy of Pentahelix, namely academics, universities, industry, government, community and media is an important factor in achieving development success. Pentahelix is expected to be able to synergize well so that regional economic development targets with a local wisdom approach in the digital era can be achieved. The problem in Tana Toraja Regency is the lack of business development, especially Micro, Small and Medium Enterprises (MSMEs), even though the tourism business in Tana Toraja has extraordinary potential. The beauty of various cultural tourism destinations, coffee products and high-quality woven fabrics. This potential should provide opportunities for MSMEs to succeed but it is difficult to develop their business. Based on this, a pentahelix collaboration strategy is needed to develop the potential of MSMEs in the Tana Toraja tourist destination area. The method of community service through stages: (1) exploration with all elements of the pentahelix (2) socializing the pentahelix synergy in the national seminar forum (3) observing problems in the Toraja area (3) initial survey of MSME development needs in Toraja (4) implementation of service with MSME partners. The output obtained from the implementation of this Service and Empowerment Program is to increase the knowledge (capacity building) and skills (soft skills) of entrepreneurs in the development of MSMEs in the Tana Toraja Regency area.